Nano agrochemical zinc oxide influences microbial activity, carbon, and nitrogen cycling of applied manures in the soil-plant system. (15th January 2022) - Shah, Ghulam Mustafa; Ali, Hifsa; Ahmad, Iftikhar; Kamran, Muhammad; Hammad, Mohkum; Shah, Ghulam Abbas; Bakhat, Hafiz Faiq; Waqar, Atika; Guo, Jianbin; Dong, Renjie; Rashid, Muhammad Imtiaz
Abstract: The widespread use of nano-enabled agrochemicals in agriculture for remediating soil and improving nutrient use efficiency of organic and chemical fertilizers is increasing continuously with limited understanding on their potential risks. Recent studies suggested that nanoparticles (NPs) are harmful to soil organisms and their stimulated nutrient cycling in agriculture. However, their toxic effects under natural input farming systems are just at its infancy. Here, we aimed to examine the harmful effects of nano-agrochemical zinc oxide (ZnONPs) to poultry (PM) and farmyard manure (FYM) C and N cycling in soil-plant systems. These manures enhanced microbial counts, CO2 emission, N mineralization, spinach yield and N recovery than control (unfertilized). Soil applied ZnONPs increased labile Zn in microbial biomass, conferring its consumption and thereby reduced the colony-forming bacterial and fungal units. Such effects resulted in decreasing CO2 emitted from PM and FYM by 39 and 43%, respectively. Further, mineralization of organic N was reduced from FYM by 32%, and PM by 26%. This process has considerably decreased the soil mineral N content from both manure types and thereby spinach yield and plant N recoveries. In the ZnONPs amended soil, only about 23% of the applied total N from FYM and 31% from PM was ended up in plants, whereas the respective fractions in the absence of ZnONPs were 33 and 53%. Hence, toxicity of ZnONPs should be taken into account when recommending its use in agriculture for enhancing nutrient utilization efficiency of fertilizers or soil remediation purposes. Highlights: Agro-nano zinc oxide (ZnONPs) toxicity was studied on C and N cycling from manures. Poultry (PM) and farmyard manures (FYM) were selected for this purpose. ZnONPs reduced microbial biomass and colony forming units in manures amended soil. These NPs decreased CO2 emission, and N mineralization from manures. Spinach N recovery decreased by 41 and 30% from PM and FYM, respectively.